Knowledge practices and student access and success in General Chemistry at a Large South African University - Mtombeni, Thabile Nokuthula (Rhodes University, Faculty of Education, Department of Education, 2018)
This dissertation reports on an investigation into the structuring principles of the General Chemistry curriculum at a Large South African University (LSAU). Student learning in the introductory modules of General Chemistry is critical for access to a range of fields since it is a requisite course for a variety of degree programmes. However, there is ample evidence that success in this subject remains a major challenge, particularly for black students. My quest in this study was to explore how the curriculum could enable greater epistemic access and thus include more students in science programmes at the LSAU. I investigated the organising principles underlying the curriculum practices of the General Chemistry module and explored the effects of the curriculum structure on student learning. Theoretically and conceptually, the study was underpinned by a social realist approach which holds that knowledge is stratified, differentiated, and has real emergent properties, powers and effects. The research question that I attempted to answer in this study was: How do knowledge practices privileged in the General Chemistry curriculum at the LSAU enable or constrain student learning? I adopted an intensive research design approach to conduct a qualitative case study using social realism and LCT as theoretical and analytical lenses. I used empirical data such as curriculum documents and interviews with lecturers to uncover the underlying generative mechanisms of the curriculum. I adopted a multi-layered data analysis process to make visible the underlying organising principles informing knowledge practices in the curriculum so that I could explain their potential effects on student learning. The first level of analysis explored the context of the curriculum and associated knowledge practices, and examined the pedagogic discourse evident in the curriculum. The second level of analysis revealed the inner logic structuring the curriculum and the associated knowledge practices. I used Maton's Legitimation Code Theory (LCT): Specialisation to identify the specialisation codes, gazes and insights generated by the curriculum. For the third level of analysis, LCT: Semantics was used to generate the semantic profiles of learning activities to determine the extent to which the curriculum structure made cumulative learning possible. From the findings, it is evident that the verticality of knowledge in General Chemistry points to a recontextualising principle that prescribes the selection and arrangement of knowledge, and the special relationship of actors and discourses. As a result, the strong framing of the instructional discourse of General Chemistry curriculum structure is likely to constrain epistemological access for large numbers of students. In order to improve epistemological access to the field, weaker framing of the instructional discourse in introductory science is necessary. Weaker framing of the General Chemistry curriculum would require, in particular, changes to pacing, and that the evaluative criteria are made explicit. This is especially necessary when certain abstract and complex curricular content is taught, especially in the first semester. The findings also indicate that the nature of the organising principles in the curriculum are significant for improving epistemological access to knowledge. In terms of LCT: Specialisation, the General Chemistry curriculum generated a knowledge code and downplayed differences among social categories of students, thus positioning all equally in relation to the knowledge and practices of the field. Therefore, the structuring of the curriculum emphasises and legitimates students who have attained specialist knowledge without considering the nature of the new student coming into the educational setting. Simply, what is privileged is both the object of study (theoretical knowledge) and how it is studied (procedural knowledge). This finding is in line with the general outcomes of Chemistry education. In addition, the purist insight generated by the curriculum further attests to where the emphasis is placed in the curriculum. I argue that the lack of social relations in the curriculum poses a challenge for the holistic development of students as science knowers. The analysis of the learning activities shows rapid code shifts that indicate changes in cognitive demand and modes of thinking required of students. I argue that signposting the changes in complexity of knowledge and in the mode of thinking required could make learning, and thus epistemological access, more possible. Given the imperative of access to powerful knowledge, I contend that the curriculum should be reshaped to enable epistemological access for more students.
Keywords: Chemistry -- Study and teaching (Higher) -- South Africa; Knowledge management; Education, Higher -- Curricula -- South Africa; Critical realism; Social integration -- South Africa; Educational equalization -- South Africa